2018
DOI: 10.1371/journal.pntd.0006193
|View full text |Cite
|
Sign up to set email alerts
|

Presence of B. thailandensis and B. thailandensis expressing B. pseudomallei-like capsular polysaccharide in Thailand, and their associations with serological response to B. pseudomallei

Abstract: BackgroundBurkholderia pseudomallei is an environmental Gram-negative bacillus and the cause of melioidosis. B. thailandensis, some strains of which express a B. pseudomallei-like capsular polysaccharide (BTCV), is also commonly found in the environment in Southeast Asia but is considered non-pathogenic. The aim of the study was to determine the distribution of B. thailandensis and its capsular variant in Thailand and investigate whether its presence is associated with a serological response to B. pseudomallei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
(73 reference statements)
1
21
0
Order By: Relevance
“…Twelve of seventeen B. thailandensis -positive samples were found at different study sites, but in several cases both B. thailandensis and B. pseudomallei were detected in the same site. This is consistent with findings from a Thai study [56].…”
Section: Discussionsupporting
confidence: 93%
“…Twelve of seventeen B. thailandensis -positive samples were found at different study sites, but in several cases both B. thailandensis and B. pseudomallei were detected in the same site. This is consistent with findings from a Thai study [56].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a recent epidemiologic study showed high prevalence of environmental B. pseudomallei in rice paddy fields across multiple regions of Thailand, especially in the east (6). Subsequent serologic responses against B. pseudomallei in healthy rice farmers are associated with exposure to environmental B. pseudomallei rather than B. thailandensis and BTCV (20); the cause could be a higher prevalence of B. pseudomallei. It is impossible to distinguish between the serologic responses to B. pseudomallei and BTCV because CPS components are highly cross-reactive (9).…”
Section: Discussionmentioning
confidence: 99%
“…Healthy persons who live in melioidosis-endemic areas, on the other hand, primarily demonstrate cellular immune cross-reactivity. We recommend further investigation of human immune responses in healthy persons where the less pathogenic strains are prevalent, such as in the central and eastern parts of Thailand (20). It is possible that exposure to the less virulent B. thailandensis and BTCV generates immune cross-reactivity, which could confer some protection against melioidosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the existence of cross-reactive antibody responses has not been clearly established, since previous studies have not been able to demonstrate cross-reactive IHA titers between Bp and Bt in healthy controls. 23 , 24 We are presently exploring the contribution of cross-reactivity to antibody responses in our laboratory.…”
Section: Discussionmentioning
confidence: 99%